Back to the future : The evolution of Sun Microsystems business model (1982 to 2007) - Chesbrough, Henry William; Constantinides, Margarita (London : SAGE Publications Ltd, 2017)
This case study outlines the time period between 1982 and 2007 of Sun Microsystems. The case showcases the company's long history with open source software and open innovation, as well as its history of proprietary software and proprietary technology. With the company's announcement in 2006 that it would make much of its proprietary software available under open source terms, the company was again re-entering an open innovation phase, with the hope that the strategy would drive adoption of its software and thus increase revenue and profitability. By 2007, Sun Microsystems seemed to be on a path back to its more open technology roots and the case study ends at that point in the company's history.
Originally published in Chesbrough, H., & Constantinides, M. (2008). Back to the future: The evolution of Sun Microsystems business model (1982 to 2007). The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sun Microsystems; Business planning -- Case studies; Open source software -- Case studies